Designing Mobile-Assisted Language Learning to Improve Reading Skills and the Vocabulary Mastery of Legal Terms - Surdyanto, Annas (Aufklarung: Jurnal Pendidikan, Sosial dan Humaniora, 2023)
English in Indonesia has been an important capital in all aspects of life. Currently, there is so much information delivered in English. Currently, In Indonesia, English learning media are too concentrated for general language use. Therefore, in order to solve the problem above, there must be learning media that not only cover the field of law but also motivate students to enhance their reading frequency in order to improve their vocabulary mastery. To improve students’ vocabulary mastery and reading skills as well as gaining learning motivation, there are many ways that can be applied. One of them is by providing learning materials by making use of the current developing technology. This research is intended to design a mobile-assisted language learning to improve reading skills and mastery of legal terms vocabulary and purposively addressed to an Indonesian youth community located in South Tangerang, Banten, Indonesia. The employed interview has resulted in a well-designed mobile assisted language learning program that has been tested through the usability testing and questionnaire analysis.